Polymicrobial biofilms: Impact on fungal pathogenesis - Costa-Orlandi, Caroline Barcelos [UNESP] (2022)
The formation of sessile communities called biofilms is a significant factor in the chronicity of infections caused by different microorganisms, fungi, bacteria, viruses, or protozoa. This phenomenon is considered the major cause of persistent nosocomial infections, of high virulence and recalcitrant to treatments, especially in immunocompromised patients who use devices such as catheters, contact lenses, prostheses, heart valves, dentures, among others. The biofilm phenotype promotes several advantages to microorganisms caused by physical and genetic factors and protects against the host’s immune system through impaired activation of phagocytes and the complement system. In addition, for its eradication, it is necessary to increase the concentration of antibiotics from 100 to 1000 times compared with planktonic cells. It is known that persistent chronic infections in different parts of the human body such as lungs, oral cavity, middle ear, genitourinary tract, nails, surgical or chronic wounds originate from polymicrobial biofilms, which commonly lead to worse prognoses. Interactions between microorganisms are dependent on the environment in which they are found and are highly complex. They can compete antagonistically for nutrients and adhesion sites, but they can coexist in cooperative ways, supporting their mutual development neutrally or synergistically. This chapter will address aspects related to polymicrobial biofilms to unravel the exchange of functions in different interspecies or even in interkingdom conjunctions and their role in pathogenesis.